2009
DOI: 10.1038/modpathol.2009.13
|View full text |Cite
|
Sign up to set email alerts
|

Gynecological tumors in Mulibrey nanism and role for RING finger protein TRIM37 in the pathogenesis of ovarian fibrothecomas

Abstract: Mulibrey nanism is an autosomal recessive growth disorder caused by mutations in the TRIM37 gene encoding a protein of unknown function. More than half of female patients with Mulibrey nanism develop benign mesenchymal tumors of ovarian sex cord-stromal origin. In this work, we characterize the gynecological tumors of female patients with Mulibrey nanism in detail. In addition to tumors of the fibrothecoma group, 18% (4/22) of the patients were observed with epithelial neoplasias, including 2 ovarian adenofibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…The TRIMs family has been identified to be involved in the progression, transformation, autophagy and metastasis of cancer (2226). Previous studies have demonstrated altered expression levels of TRIM37 in breast and ovarian cancer, which confirmed its oncogenic function (8,9). The present study used RT-qPCR, immunostaining and western blotting to determine that the increased expression of TRIM37 occurred at the transcriptional and post-transcriptional levels in CRC, suggesting that it may contribute to the progression of malignancies.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The TRIMs family has been identified to be involved in the progression, transformation, autophagy and metastasis of cancer (2226). Previous studies have demonstrated altered expression levels of TRIM37 in breast and ovarian cancer, which confirmed its oncogenic function (8,9). The present study used RT-qPCR, immunostaining and western blotting to determine that the increased expression of TRIM37 occurred at the transcriptional and post-transcriptional levels in CRC, suggesting that it may contribute to the progression of malignancies.…”
Section: Discussionsupporting
confidence: 60%
“…TRIM37 was also revealed to be associated with polycomb repressive complex 2, and may lead to extensive changes in gene expression, including the silencing of some tumor suppressor genes (8). Previous studies revealed that TRIM37 may undergo amplification in ovarian cancer (9) and may promote transformation in breast cancer (8). Additionally, the upregulation of TRIM37 promoted the growth and migration of cancer cells of pancreatic cancer (10).…”
Section: Introductionmentioning
confidence: 99%
“…Mulibrey ( mu scle, li ver, br ain, and ey e) nanism is a rare, autosomal recessive growth disorder with prenatal onset that includes severe growth retardation, distinct dysmorphic features, constrictive pericarditis, hepatomegaly, male infertility, insulin resistance, and metabolic deficiencies (19,20). There are approximately 130 cases known worldwide with 89 originating from Finland (19).…”
Section: Genetic Summarymentioning
confidence: 99%
“…There are approximately 130 cases known worldwide with 89 originating from Finland (19). Mulibrey nanism is caused by biallelic mutations in TRIM37 on chromosome 17q22.…”
Section: Genetic Summarymentioning
confidence: 99%
See 1 more Smart Citation